Breve histórico das mudanças na regulaç\~ao do trabalho no Brasil - André Gambier Campos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The phenomenon of inequality is typical of relations that structure class society and capitalism. Workers and entrepreneurs, subjects of those relations, are in a position of inequality, which derives from the following facts: on the one hand, entrepreneurs are collective subjects, because their decisions affect society as a whole. Furthermore,workers are individual subjects, with all the weaknesses and difficulties of this condition, because their choices don't affect almost anything beyond their own community. Although it is not possible to overcome this inequality, it is possible to think about its mitigation, through public regulation of labor relations. Founder of rights and duties in the labor market, such regulation seeks to mitigate the structural inequality observed between both subjects. This discussion paper seeks to recover the basic features of the evolution of labor regulation in Brazil, in the broad historical spectrum ranging from the 1930s to 2000s.
Keywords: J80; J83; J88; 330; labor; labor regulation; labor legislation